P577 Drug Induced Liver Injury (DILI) secondary to biologic therapy in IBD: ECCO- CONFER Series. (25th January 2019) - Lisle, J; Myers, S; Pugliese, D; Raine, T; de Vries, A C; Katsanos, K; Filip, R; Karmiris, K; Sebastian, S
Abstract: Background: Drug-induced liver injury (DILI) in IBD patients is mostly attributed to thiopurines and methotrexate. Less has been reported about biologics-related DILI in IBD patients with existing data restricted to case reports. Methods: We retrospectively collected data on a multi-centre cohort of IBD patients with DILI attributed to biologics. This was a part of the European Crohn`s and Colitis Organisation (ECCO) initiated CONFER (Collaborative Network for Exceptionally Rare case reports) project. A call was made to all ECCO members to report DILI following initiation of biologics. Data were recorded on a standardised case report form and analysed with descriptive statistics. Results: Eighteen patients with DILI attributed to biologics have so far been reported in this cohort (M: F −10:8, CD: UC- 10:8, Median age 33 years). DILI was attributed to infliximab in 15 patients, vedolizumab in 2 and adalimumab in 1. Seven patients were on concomitant immunomodulators (5 thiopurines, 2 methotrexate). Coexistent axial or peripheral arthropathy was recorded in 6 patients. Patients had a median of 3 doses (range 1–22) prior to development of DILI. Median time to DILI following last exposure to biologics was 51 days (range 12–84 days). Predominant hepatocellular pattern of liver function tests was noted in 9 patients, predominant cholestatic in 2 and mixed picture in the remaining 7. Antinuclear antibodies were present in 11/18 (3 of these anti smooth also muscle Ab positive) with elevated IgG in 9 patients. Liver biopsy was performed in 9 patients with 6 suggesting drug toxicity, 2 showing additional features of autoimmune liver disease and one showing co-existent steatohepatitis. The biologic was discontinued in all but 2 patients. Six patients had steroids following liver injury. Complete recovery of liver function was seen in 13, and partial in 3 patients following discontinuation of biologics in a median time of 35 days. Alternative biologics were started for IBD in 13 patients (10 switched from infliximab to vedolizumab, 2 from infliximab to adalimumab, and one from infliximab to ustekinemab), ) with no recurrence of DILI. In a median follow-up of 17 months, 2 patients were formally diagnosed to have autoimmune liver disease requiring additional immunosuppression. Conclusions: DILI is reported in patients receiving biologics for IBD predominantly with Infliximab with development of autoimmunity in a subset of patients. Majority recover on stopping the offending agenda with no recurrence on switching the biologics. Results should be interpreted with caution as causality could not be certain given the retrospective nature of the study. A larger cohort is required to study DILI related to biologics in IBD.